Tuning of the Lethal Response to Multiple Stressors with a Single-Site Mutation during Clinical Infection by Staphylococcus aureus - Krishan Kumar (American Society for Microbiology, 2017)
ABSTRACT The agr system of Staphylococcus aureus promotes invasion of host tissues, and as expected, agents that block agr quorum sensing have anti-infective properties. Paradoxically, agr-defective mutants are frequently recovered from patients, especially those persistently infected with S. aureus. We found that an agr deficiency increased survival of cultured bacteria during severe stress, such as treatment with gentamicin, ciprofloxacin, heat, or low pH. With daptomycin, deletion of agr decreased survival. Therefore, agr activity can be either detrimental or protective, depending on the type of lethal stress. Deletion of agr had no effect on the ability of the antimicrobials to block bacterial growth, indicating that agr effects are limited to lethal action. Thus, the effect of an agr deletion is on bacterial tolerance, not resistance. For gentamicin and daptomycin, activity can be altered by agr-regulated secreted factors. For ciprofloxacin, a detrimental function was downregulation of glutathione peroxidase (bsaA), an enzyme responsible for defense against oxidative stress. Deficiencies in agr and bsaA were epistatic for survival, consistent with agr having a destructive role mediated by reactive oxygen species. Enhanced susceptibility to lethal stress by wild-type agr, particularly antimicrobial stress, helps explain why inactivating mutations in S. aureus agr commonly occur in hospitalized patients during infection. Moreover, the agr quorum-sensing system of S. aureus provides a clinically relevant example in which a single-step change in the response to severe stress alters the evolutionary path of a pathogen during infection. IMPORTANCE When phenotypes produced in response to an environmental stress are inadequate to buffer against that stress, changes that do buffer may become genetically encoded by natural selection. A clinically relevant example is seen with S. aureus mutants that are deficient in the key virulence regulator agr. Paradoxically, defects in agr are selected during serious hospital infection and have been associated with worse outcome. The current work helps resolve this paradox: agr mutants are often less readily killed by lethal stressors without affecting MIC, a phenomenon known as tolerance. Our results indicate that tolerance, which would not be detected as resistance, can be selected in clinical settings. The data also support the ideas that (i) S. aureus broadly hedges against environmental change and stress through genome plasticity, (ii) reactive oxygen can be involved in the self-destructive response in bacteria, and (iii) therapeutic targeting of agr and virulence can be counterproductive.